Benefits and challenges of graduate start-up and academic spin-off model integration: a systematic review - Anwar Zainol, Fakhrul; Wan Daud, Wan Norhayate; Abdul Rahman, Syamsul Azri; Mohd Salleh, Safrul Izani; Ishola, Balogun Daud (International Journal of Evaluation and Research in Education (IJERE), 2025)
Government representatives and university administrators must comprehend the reasons behind academics’ desire to start their own businesses to create laws that effectively encourage academics to take up entrepreneurship. One may understand how seemingly difficult it might be to foster creativity and entrepreneurship in a varied community, considering how difficult it can be to teach entrepreneurship to university students. Consequently, the goal of this systematic review was to summarize the challenges and benefits of integration of graduate start-up and academic-spin off model. Three internet databases were searched for articles between 2010 and 2023 (i.e., a cumulative index using Scopus, the Web of Science, and Emerald to provide a summary of the challenges and benefits of graduate start-up and academic spin-off models). The study adds to a thorough understanding of the complex nature of business models by highlighting the models’ dynamic evolution over time, the value of global collaboration, the necessity of carefully examining individual models, and the strategic diversity that comes from exploring several business models simultaneously. When taken as a whole, these observations offer insightful information that decision-makers, business owners, and academics may use to better understand, traverse, and navigate the terrain of innovation and entrepreneurial processes.